Penerapan Regresi Data Panel pada Faktor-faktor yang Mempengaruhi Tingkat Kemiskinan di Provinsi Papua Barat Tahun 2018-2022 - Malawat, Jihan Rahmi; Matualage, Dariani; Matulessy , Esther Ria (Neolectura, 2024)
West Papua has consistently been one of the regions with the highest poverty rates in Indonesia, ranking second in 2022. This study investigates the factors influencing the poverty rate in West Papua from 2018 to 2022 using panel data analysis, which combines both cross-sectional and time-series data. The variables examined include the open unemployment rate, economic growth rate, and human development index. A Random Effect Model (REM) was selected as the most appropriate model for analyzing the data, given its ability to account for individual-specific effects while assuming that these effects are uncorrelated with the independent variables. The model produced a goodness of fit of 0.74, suggesting a strong explanatory power. The results indicate that the economic growth rate and human development index significantly influence the poverty rate, both showing a negative correlation with poverty levels. However, the open unemployment rate was found to be insignificant. These findings suggest that focusing on economic growth and improving human development outcomes could be key to reducing poverty in West Papua. Policy implications and recommendations for further research are also discussed.